Optimization of Forced Degradation Using Experimental Design and Development of a Stability-Indicating Liquid Chromatographic Assay Method for Rebamipide in Bulk and Tablet Dosage Form - Sandeep SONAWANE; Paraag GIDE (MDPI AG, 2016)
A novel stability-indicating RP-HPLC assay method was developed and validated for quantitative determination of rebamipide in bulk and tablet dosage form. Rebamipide (drug and drug product) solutions were exposed to acid and alkali hydrolysis, thermal stress, oxidation by hydrogen peroxide and photodegradation. Experimental design has been used during forced degradation to determine significant factors responsible for degradation and to obtain optimal degradation conditions. In addition, acid and alkali hydrolysis was performed using a microwave oven. The chromatographic method employed the HiQ sil C-18HS (250 × 4.6 mm; 5 μm) column with mobile phase consisting of 0.02 M potassium phosphate (pH adjusted to 6.8) and methanol (40:60, v/v) and the detection was performed at 230 nm. The procedure was validated for specificity, linearity, accuracy, precision and robustness. There was no interference observed of excipients and degradation products in the determination of the active pharmaceutical ingredient. The method showed good accuracy and precision (intra and inter day) and the response was linear in a range from 0.5 to 5 μg mL−1. The method was found to be simple and fast with less trial and error experimentation by making use of experimental design. Also, it proved that microwave energy can be used to expedite hydrolysis of rebamipide.